A Companion to the Eucharist in the Reformation - Wandel, Lee Palmer (Leiden : BRILL, 2013)
This collection of articles by European and American scholars offers an introduction to the Eucharist in the Reformation, as theology, liturgy, and wellspring for thinking about the relationship between the sensible world and God.
Part Three Sites of the EucharistSites of the Eucharist; Part Four The Art of the Liturgy; A View of the Eucharist on the Eve of the Protestant Reformation; The Lutheran Tradition; Reformed; Part Five The Eucharist and Sound; The Sounds of Eucharistic Culture; Part Six The Import of the Eucharist; Sacramental Poetics; Enlightenment Aesthetics and the Eucharistic Sign: Lessing's Laocoön; Bibliography; Index
Description based upon print version of record.
Keywords: Christianity and culture -- History -- 16th century; Lord's Supper -- History -- 16th century; Lord's Supper -- History -- 16th century; Christianity and culture -- History -- 16th century; RELIGION / Christian Rituals & Practice / Worship & Liturgy; RELIGION / Institutions & Organizations; Electronic books